Trans-Ancestry Mutation Landscape of Hepatoblastoma Genomes in Children - Liu, Jie; Gao, Chengwen; Wang, Liping; Jian, Xuemin; Ma, Mingdi; Li, Tong; Hao, XiWei; Zhang, Qian; Chen, Yuanbin; Zhao, Jing; Niu, Haitao; Zhu, Chengzhan; et al. (Frontiers in Oncology, 2021)
Hepatoblastoma (HB) is the most common malignant tumor in the liver of infants and young children. The incidence rate varies among different populations. However, genetic differences in HB patients with different epidemiological and ancestral backgrounds have not been found. In this study, we aim to analyze data from 16 patients treated at our center and collected published data from whole-exome sequencing studies on HB, and to explore the genetic differences between races. Data from a total of 75 HB patients of three races (24 Asian, 37 Caucasian and 14 Hispanic) were analyzed. We identified 16 genes with recurrent somatic mutations and 7 core pathway modules. Among them, the Wnt/β-catenin pathway had the highest mutation rate, and the mutation frequency in Caucasians and Hispanics was approximately twice as high as that in Asians. In addition, this study compared the characteristics of gene mutations between patients who underwent preoperative chemotherapy and those who did not and found that there was no significant difference in gene mutations between the two groups. We also preliminarily verified the function of cancer-associated candidate genes (CTNNB1 and KMT2D). In conclusion, we found ethnic differences in HB biology at the genomic level, which expands our understanding of the genetics of HB in children.